Rehabilitation And Reconstruction Of Islamic Architectural Heritage In China: The Example Of The Ningxia Hui Autonomous Region - François N. Dubé; Huang Lijun (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
The Ningxia Hui Autonomous Region, located in Northwestern China, has the highest concentration of Hui Muslims in China: around 34% of the local population is Hui Muslim. Following the anti-religious campaigns of the communist regime and the wide destruction of the Cultural Revolution, Hui Muslims began gradually to reclaim their Muslim heritage in the late 70's. A major aspect of the rediscovery of their Islamic heritage was the Rehabilitation and reconstruction of Islamic Architectural buildings. As of today, Ningxia counts 4,500 mosques and other religious buildings. The present article seeks to introduce the architectural tendencies at play in this reconstruction, specifically the role of competing Arabic and Chinese influences.